Approximate synthesis for LUT count reduction via probabilistic error propagation - Schlögl, Thomas; Keszocze, Oliver (it - Information Technology, 2025)
Approximate computing is an fast developing area for resource-efficient and fast designs that trades off computational accuracy with non-functional aspects such as delay, energy requirements or area. It can be used for applications where it is acceptable to compute inaccurate results such as image processing. A lot of work has been published on approximate synthesis for ASICs. As FPGAs are becoming more prevalent, approximation techniques for this technology should be developed. Lookup tables are a scarce resource on FPGAs. Consequently, we present and evaluate multiple approaches for reducing the number of lookup tables required to implement a given design on an FPGA. Our approaches work by removing either wires or entire lookup tables from a lookup table network. We can show that our approach is faster than related work while removing a comparable number of lookup tables (more in most cases
Keywords: approximate computing; FPGA; logic synthesis; optimization